Estudio en caninos de zonas urbanas de Tandil como posibles portadores de Escherichia coli verocitotoxigénicos - Fernández, D. (2006)
The aim of this study was to investigate if dogs of urban areas would constitute a risk for humans as carriers of verocytotoxin-producing Escherichia coli in spite to the care?s habits to which these animals are subjected. Fecal swabs were collected from the rectum of sixty dogs and examined for the presence of verocytotoxin-producing Escherichia coli. The method of screening was based on the polymerase chain reaction technique to detect genes encoding type 1 and 2 verocytotoxins. All samples showed to be negative for verocytotoxin-producing Escherichia coli. This result may be due to the current care?s habits of urban dogs that could reduce the possibility of contact and colonization with verocytotoxin-producing Escherichia coli. This hypothesis must be confirmed carrying out another similar study with rural dogs which receive different care that urban dogs. This would allow to establish a relationship between dogs current care habits and its role as verocytotoxin-producing Escherichia coli.